Analisis Intensitas Medan Listrik pada Pemukiman akibat Sambaran Petir pada Menara Base Transceiver Station Analysis of Electric Field Intensity in Residential Areas Due to Lightning Strikes on Base Transceiver Station Towers - Ni Made Seniari; Supriyatna; Abdul Natsir; Ida Ayu Sri Adnyani; I Made Ginarsa; Muh. Sultanul Mahdi; Haidar Hamdi; Bagus Widhi Dharma S (Jurnal Penelitian Pendidikan IPA, 2025)
Base Transceiver Station (BTS) towers are highly vulnerable to lightning strikes. A lightning strike is a moving electric charge that generates an electric field and a magnetic field, both of which are vector quantities, and induces voltage around the tower. The closer to the tower, the greater the values of the electric field, magnetic field, and induced voltage generated. A 49-meter highs tower in Mataram City is located 25 and 300 meters from residential areas and public facilities. The metabolism of living organisms, such as blood circulation, nerve function, heart rate, lung function, cell growth, and cell division, are also vector quantities. Exposure of living organisms to external electric fields exceeding the threshold of ≥10 kV/m can disrupt their metabolism. It is crucial to determine the magnitude and direction of the electric field vector caused by lightning strikes on BTS towers and how it affects living organisms around the tower. Observations are based on Coulomb's Law and its derivative theories on electric fields. The peak lightning current in tropical areas ranges from 10 to 100 kA, with a frequency of 200 kHz. The electric field intensity at distances of 25 and 300 meters is 58.30, 584.50, 4.86, and 48.71 kV/m, respectively. These results indicate that a distance of 25 meters from the tower is not safe from exposure to high electric field intensity values.